PENGARUH PEMBERIAN UMPAN BALIK REKAMAN VIDEO DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MICRO TEACHING MAHASISWA - Mochtar M Noor (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2009)
This experimental research aimed at finding out the impact of video recorded feedback on and motivation to the learning achiement in microteaching. The research was conducted at Teachers Education Faculty of Prof. Dr. Hamka in Jakarta. The research samples were selected ny apllying two stage cluster random sampling technique to obtain 60 students from two classes. The results of the research approved the hypotheis that the video taped feedback and motivation had positive impact to the learning achievement in microteaching.